Onomatopoeia Found in Shazam Comic - Langus , Natalia; Sulatra, I Komang; Utami, Ni Made Verayanti (Journal of Language and Applied Linguistics, 2023)
This study aims to find out the type of onomatopoeia used in the comic and analyse the meaning of the onomatopoeic word. The data were taken from Shazam comic written by Geoff Johns. Observation method was used in collecting the data with several steps applied such as reading, identifying and note taking the onomatopoeic words. This study applied descriptive qualitative method to analyse the data. The theory of types of onomatopoeia by Bredin (1996) was used to analyse the data. This study found fifty five (55) onomatopoeia. Those onomatopoeia words are divided into three types, such as 28 data of direct onomatopoeia, 14 data of associative onomatopoeia, 13 data of exemplary onomatopoeia. Direct onomatopoeia became dominant type used because the comic tells about superhero against enemies who want to destroy the world. The use of onomatopoeia in comic is very important since comic is sequential series of image with character and conversation inside.